Post-stroke depression inhibits improvement in activities of daily living in patients in a convalescent rehabilitation ward - Tsuchiya, Kenji (J Phys Ther Sci, 2016)
[Purpose] There have been no investigations into the improvement of activities of daily living among patients suffering from post-stroke depression on admission to convalescent rehabilitation wards in Japan. This study aimed to assess the improvement of activities in daily living in patients with or without post-stroke depression at the time of admission to a convalescent rehabilitation ward. [Subjects and Methods] This retrospective study included 108 stroke patients divided into two groups according to their Geriatric Depression Scale 15-item short form scores. Activities of daily living were assessed using the Functional Independence Measure. The degree of improvement on the Functional Independence Measure was defined as the difference between scores on admission and at discharge. [Results] The Functional Independence Measure gain score was significantly different from the Functional Independence Measure total score. There was a significant interaction between time period and post-stroke depression factors for the Functional Independence Measure total score. A multiple regression analysis revealed a significant association between Geriatric Depression Scale score and Functional Independence Measure total score. [Conclusion] The present study suggests that post-stroke depression has a negative impact on recovery of activities of daily living and on rehabilitation outcomes in a convalescent rehabilitation ward setting.